Comparative reliability study on classification of femoral intertrochanteric fractures by using Tang and Japanese new typing systems based on 3-D CT and Evans-Jensen and AO/OTA-2018 classical typing systems based on X-ray. Issue 3 (September 2022) - Pang, Bin; Li, Fei; Zhong, Chuanli; Weng, Xuan; Xu, Hongfei; Yang, Tao; Wang, Xiaolin; Wang, Ye; He, Liying; Zhu, Qiuhong
Abstract: Objective: To analyze and compare the reliability of two new three-dimensional classifications of intertrochanteric fractures based on three-dimensional computed tomography (3-D CT) and two traditional classifications based on X-ray. Methods: X-ray and 3-D CT image data of 105 patients with intertrochanteric fractures were collected. Four orthopedic surgeons as observers used Evans-Jensen, AO/OTA-2018, Tang and Japanese new classification systems to classify the classification. Two months later, the original imaging data were renumbered, and the same methods was used for the classification again. κ test was used to evaluate the inter-observer and intra-observer consistency of each classification. Results: The inter-observer κ values of Evans-Jensen, AO/OTA-2018, Tang and Japanese new classifications were 0.91 (range 0.87–0.95), 0.90 (range 0.88–0.92), 0.93 (range 0.89–0.95) and 0.91 (range 0.89–0.93), respectively. There was no significant difference between Evans-Jensen and AO/OTA-2018 classification systems ( p  > 0.05) but were significant differences between Evans-Jensen and Tang, Evans-Jensen and Japanese new, AO/OTA-2018 and Tang, AO/OTA-2018 and Japanese new, Tang and Japanese new classification systems ( p  < 0.05). Conclusion: Based on three-dimensional CT, compared with the traditional classification of femoral intertrochanteric fractures, the two new classifications are more reliable.